Synthesis and photovoltaic properties of copolymers with a fluoro quinoxaline unit. Issue 8 (30th January 2018) - Song, Suhee; Kim, Seungmin; Kim, Wonjun; Park, Seong Soo; Park, Sung Heum; Jin, Youngeup
ABSTRACT: Two novel accepter units, namely, difluoroquinoxaline and monofluoroquinoxaline, were prepared and used for the synthesis of the conjugated polymers containing electron donor–acceptor pairs for use in organic photovoltaics. The introduction of a fluorine atom into the quinoxaline moiety resulted in polymers with lowered highest occupied molecular orbital (HOMO) energy levels; this increased the open circuit voltage of the devices based on the synthesized polymers. The conjugated polymers containing difluoroquinoxaline and monofluoroquinoxaline, namely, thiophene and benzodithiophene, were synthesized using the Stille polymerization reaction to produce PEHBQxF2, PEHBQxF1, PEHBDTQxF2, and PEHBDTQxF1. The HOMO energy levels of PEHBQxF2, PEHBQxF1, PEHBDTQxF2, and PEHBDTQxF1 were determined to be −5.66, −5.52, −5.54, and −5.39 eV, respectively. The device with PEHBDTQxF2/PC71 BM (1:2, w/w) and containing diiodooctane (3 vol %) exhibited the best photovoltaic performance, with its V OC being 0.79 V, J SC being 10.44 mA/cm 2, FF being 68%, and PCE being 5.58%. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 821–830 Abstract : Two novel acceptor units, namely, difluoroquinoxaline and monofluoroquinoxaline, were prepared and used for the synthesis of conjugated polymers containing electron donor–acceptor pairs for use in organic photovoltaics.